Superresolution Microscopy Reveals Distinct Phosphoinositide Subdomains Within the Cilia Transition Zone - Conduit, Sarah E.; Davies, Elizabeth M.; Fulcher, Alex J.; Oorschot, Viola; Mitchell, Christina A. (Frontiers in Cell and Developmental Biology, 2021)
Primary cilia are evolutionary conserved microtubule-based organelles that protrude from the surface of most mammalian cells. Phosphoinositides (PI) are membrane-associated signaling lipids that regulate numerous cellular events via the recruitment of lipid-binding effectors. The temporal and spatial membrane distribution of phosphoinositides is regulated by phosphoinositide kinases and phosphatases. Recently phosphoinositide signaling and turnover has been observed at primary cilia. However, the precise localization of the phosphoinositides to specific ciliary subdomains remains undefined. Here we use superresolution microscopy (2D stimulated emission depletion microscopy) to map phosphoinositide distribution at the cilia transition zone. PI(3,4,5)P3 and PI(4,5)P2 localized to distinct subregions of the transition zone in a ring-shape at the inner transition zone membrane. Interestingly, the PI(3,4,5)P3 subdomain was more distal within the transition zone relative to PtdIns(4,5)P2. The phosphoinositide effector kinase pAKT(S473) localized in close proximity to these phosphoinositides. The inositol polyphosphate 5-phosphatase, INPP5E, degrades transition zone phosphoinositides, however, studies of fixed cells have reported recombinant INPP5E localizes to the ciliary axoneme, distant from its substrates. Notably, here using live cell imaging and optimized fixation/permeabilization protocols INPP5E was found concentrated at the cilia base, in a distribution characteristic of the transition zone in a ring-shaped domain of similar dimensions to the phosphoinositides. Collectively, this superresolution map places the phosphoinositides in situ with the transition zone proteins and reveals that INPP5E also likely localizes to a subdomain of the transition zone membrane, where it is optimally situated to control local phosphoinositide metabolism.